Science of nanofibrous scaffold fabrication: strategies for next generation tissue-engineering scaffolds. (February 2009) - Madurantakam, Parthasarathy A; Cost, Christopher P; Simpson, David G; Bowlin, Gary L
Native extracellular matrix (ECM) provides structural support to the multicellular organism on a macroscopic scale and establishes a unique microenvironment (niche) to tissue- and organ-specific cell types. Both these functions are critical for optimal function of the organism. These natural ECMs comprise predominantly fibrillar proteins, collagen and elastin and are synthesized as monomers but undergo hierarchical organization into well-defined nanoscaled structural units. The interaction between the cells and ECM is dynamic, reciprocal and essential for tissue development, maintenance of function, repair and regeneration processes. Tissue-engineering scaffolds are synthetic, biomimetic ECM analogues that have great promise in regenerative medicine. Ongoing efforts in mimicking the native ECM in terms of composition and dimension have resulted in three strategies that permit the generation of scaffolds in nanometer dimensions. Although excellent reviews regarding the applications of these strategies in tissue engineering are available, a comprehensive review of the science behind these fabrication techniques does not exist. This review intends to fill this critical gap in the existing knowledge in the fast-expanding field of nanofibrous scaffolds. A thorough understanding of the fabrication processes would enable us to better exploit available technologies to produce superior tissue-engineering scaffolds.